Variation of the ratio of nitrate to non-seasalt sulfate in precipitation over East Asia with emissions from China. (October 2015) - Itahashi, Syuichi; Uno, Itsushi; Hayami, Hiroshi; Fujita, Shin-ichi
Abstract: Changes in anthropogenic emissions in East Asia will cause substantial variations in the precipitation chemistry. In particular, the effects of changes in China, where NOx emissions have been rising continuously and SO2 emissions peaked in 2005–2006, are important. The absolute chemical concentration in precipitation is inherently linked to the amount of precipitation; therefore, in this work we used the ratio of nitrate ( NO 3 − ) to non-seasalt sulfate nss-SO 4 2 - concentration in precipitation on an equivalent basis (hereinafter, Ratio ). Here, we extend the method in our previous study (Itahashi et al., 2014a) to Korea and China. We analyzed the long-term behavior of Ratio in precipitation during 2000–2011 and investigated the factors responsible for variations of Ratio in precipitation by using a model simulation with sensitivity analysis for emission changes in China. Ratio over Japan, Korea, and China decreased slightly or remained constant during 2000–2005 (first 6 years of 2000–2011) and subsequently increased during 2006–2011 (last 6 years of 2000–2011). Linear regression analysis of the observations showed significant increases in Ratio during 2006–2011: +3.4 ± 1.0%/year,  +13.2 ± 4.1%/year, and +9.8 ± 2.5%/year for Japan, Korea, and China, respectively (each p < 0.05). These variations in Ratio corresponded closely to the changes in the NOx/SO2 emission ratio in China. This suggests that anthropogenic emissions from China were responsible for most of the variation in precipitation chemistry in East Asia. Model simulations for 2000–2011 and their reproducibility were validated by comparison with the observation dataset, and they captured the observed features well. Sensitivity analysis of emissions from China in the model simulation for 2009–2011 clarified that the increase in NOx emissions from China contributed to 55–60% of the increase in Ratio in China and around 50–55% in Korea and Japan; the contribution of the increase in NOx emissions was smaller in the region downwind of China. In contrast, the decline in SO2 emissions from China contributed below 40% in China and around 40–45% in Japan; the effect was larger in the region downwind of China. Graphical abstract: Highlights: Ratio of nitrate to non-seasalt sulfate in precipitation was examined. Precipitation and its chemical composition are well simulated over East Asia. Ratio increased dramatically during 2006–2011 by 5–10%/year in East Asia. Increment of NOx emissions in China mainly increased the ratio in China. Decline of SO2 emissions in China effected to ratio increases in Korea and Japan.